Malawi : First Review Under the Extended Credit Facility Arrangement, Request for Waiver of Performance Criterion, and Modification of Performance Criteria-Staff Report; Informational Annex; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report ;, 2013)
This collection of papers reviews Malawi's economic performance under a program supported by the Extended Credit Facility (ECF). Drought conditions in parts of the country have dampened the near-term outlook for growth and have resulted in food insecurity for nearly 2 million inhabitants. The authorities have therefore implemented strong adjustment measures to address Malawi's substantial external and internal imbalances. The IMF Executive Board has also decided to enable the immediate disbursement of an amount equivalent to SDR 13.02 million (about USD 20 million), bringing total disbursements under the program to an amount equivalent to SDR 26.04 million (about USD 40.1 million), which will help Malawi to accelerate growth under the ECF.